EVALUATION OF QUALITY OF RAW FEED INGREDIENTS FOR ANIMAL FEED PRODUCTION - K. Ayyappan; R. Suresh; M. Palanivel; M. Ramachandran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Samples of feed ingredients were collected from the truck loads that arrived at feed processing unit located in Veterinary College and Research Institute, Orathanadu, Thanjavur, Tamil Nadu, India. Physical examination of collected samples was carried out prior to their chemical evaluation. Chemical evaluation of feed samples revealed that moisture content in maize grain ranged from 8.47% to 17.25% and high moisture was observed in samples received during the monsoon season (September to December). The crude protein content of protein supplements viz., soyabean meal, coconut oil cake, coconut deoiled cake (DOC), groundnut cake, groundnut deoiled cake, delinted decorticated cotton seed cake, sunflower deoiled cake and gingelly oil cake were 45.49, 25.11, 24.47, 36.92, 43.89, 35.36, 30.21 and 29.89 per cent on dry matter basis, respectively. The crude protein (% DMB) and crude fiber (% DMB) content of deoiled rice bran, rice bran and wheat bran were 15.47 and 16.13, 7.55 and 36.26, 14.26 and 9.47, respectively. Due to the high moisture content in maize grain 8.77% of the total truck loads of this ingredient received at the processing unit were rejected. Similarly, of the total truck loads of oil cakes received at the processing unit 20.93 % of soyabean meal, 12.5% of coconut oil cake, 20 % of coconut DOC, 22.22% of cotton seed cake and 33.33% of gingelly oil cake were rejected due to the lower crude protein and higher crude fiber contents. All truck loads of rice bran (100 %) were rejected due to their lower crude protein, higher crude fiber and Acid Insoluble Ash (AIA) content. The study thus revealed that quality control measures are essential to check the entry of poor quality raw materials before processing the feed.